Evaluating the impact of large-scale nucleic acid testing and home quarantine on a novel emerging infectious disease prevention and control: a dynamic modeling approach - Guo, Zuiyuan; Chen, Yuheng; Xiao, Guangquan; Jiang, Huawei; Yang, Zurong; Li, Jiangfan; Gong, Lili; Jin, Meisong; Wang, Feng (Frontiers in Public Health, 2025)
IntroductionConducting large-scale viral nucleic acid testing and isolating SARS-CoV-2-infections were crucial strategies in China, which played a key role in successfully controlling multiple waves of the Omicron epidemic. To thoroughly analyze the mechanisms and value of these measures, including testing and isolation, in epidemic prevention and control, and to provide a theoretical basis for scientific epidemic prevention and precise strategies in the face of potential future outbreaks of novel respiratory infectious diseases.MethodsWe developed an individual-based computational model of infectious disease dynamics. The model simulates regular large-scale nucleic acid testing for community residents during an epidemic. When individuals tested positive, they and their household members, as close contacts, are subjected to home isolation. During home isolation, the virus is assumed not to spread outside the household, but the potential for transmission within the household remained. Isolation measures can be lifted once the testing results turned negative. Finally, sensitivity analysis was conducted to verify the scientific validity and reliability of the model.ResultsThe study found that the efficacy of testing and isolation in epidemic prevention is closely related to the speed of disease transmission. When the basic reproduction number (R0) is less than 3, these measures can significantly reduce the infection rate among the population and the speed of epidemic spread; otherwise, they fail to achieve the goal of controlling the epidemic.DiscussionReducing person-to-person contact is crucial for epidemic prevention and control. In addition to testing and isolation, comprehensive non-pharmaceutical interventions (NPIs) should also be implemented, such as increasing social distancing, restricting gatherings in public places, and promoting vaccination, to control the transmission of the epidemic.